2022
DOI: 10.1007/s00170-022-08807-y
|View full text |Cite
|
Sign up to set email alerts
|

Direct metal laser sintering of Ti-6Al-4V parts with reused powder

Abstract: Ti-6Al-4V alloy is characterised by having excellent mechanical properties and corrosion resistance combined with low specific weight and biocompatibility. This material is ideal for many high-performance engineering applications. It is increasingly used in additive manufacturing (AM) thanks to the possibility of producing very complex lightweight structures, often not achievable with conventional manufacturing techniques, as well as to easily customise products according to specific customer requirements. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In a different study 13 , the porosity was found to increase in the first few cycles of reusing the powder, but it later decreased. In other studies conducted on Ti6Al4V, powder recycling was reported to have no influence on the porosity 12 and mechanical properties 23 of the final object.…”
Section: Introductionmentioning
confidence: 80%
“…In a different study 13 , the porosity was found to increase in the first few cycles of reusing the powder, but it later decreased. In other studies conducted on Ti6Al4V, powder recycling was reported to have no influence on the porosity 12 and mechanical properties 23 of the final object.…”
Section: Introductionmentioning
confidence: 80%
“…Ti-6Al-4V alloy is a well-known material for many biomedical applications due to its excellent mechanical properties, good corrosion resistance, biocompatibility, and light-specific weight [ 1 , 2 , 3 ]. Ti-6Al-4V is a double-phase (α + β) titanium alloy.…”
Section: Introductionmentioning
confidence: 99%